"Because we have lived it": Chicanx/Latinx Youth Multimodal Literacies in Youth Participatory Action Research. Issue 3 (2nd December 2021) - González Ybarra, Mónica
Abstract: This article highlights how Chicanx/Latinx youth draw on their lived realities as lenses to guide their inquiry and share their findings in a Youth Participatory Action Research project. In this project, youth collected testimonios from residents and staff within their migrant housing community to better understand histories of migration and community building. Drawing on a critical multimodal analysis framework which centers Chicanx/Latinx youth literacies and epistemologies, this article focuses on how youth drew on their community cultural knowledge and lived experiences in multimodal creation to bring attention to sociopolitical issues they cared about and impacted their community. Abstract : This article highlights how Chicanx/Latinx youth draw on their lived realities as lenses to guide their inquiry and share their findings in a Youth Participatory Action Research project. In this project, youth collected testimonios from residents and staff within their migrant housing community to better understand histories of migration and community building.